Лексико-семантичне поле «демократія» як засіб організації мовного досвіду - Чорний, І. В.; Chornyi, I. V.; ORCID: https://orcid.org/0000-0001-6079-1746; Малінська, Г.; Malinska, H. (Актуальні питання гуманітарних наук. - 2023. - Вип. 59, т. 3. - С. 161-165, 2023)
Виявлено вербалізатори лексико-семантичного поля «демократія», а також специфіки їхньої взаємодії та функціонування як мовного досвіду українського народу у текстах новинних повідомлень. Здійснено зіставний аналіз лексичних одиниць, зафіксованих у словникових дефініціях поняття «демократія», та одиниць ближньої та дальньої периферії лексико-семантичного поля, реалізованих у текстах новинних повідомлень. Основним способом виокремлення вербалізаторів аналізованого поля слугував метод ідентифікації лексичної одиниці у контекстному оточенні за допомогою SEO-програми istio, оскільки контекст відіграє важливу роль у віднесенні лексеми саме до лексико-семантичних полів. Встановлено, що семантика лексичних одиниць ближньої периферії іменника «демократія», засвідчує, що для українського народу «демократія» – це народовладдя. Окрім того, доведено, що одиниці, зафіксовані на дальній периферії лексико-семантичного поля «демократія», призначені для позначення шляху до демократичного суспільства та для вербалізації результату у досягненні демократії.

The article is devoted to the study of the verbalization of the lexical-semantic field “democracy” in the modern Ukrainian discourse on the material of the texts of news reports. The relevance of the discussed topic is determined by the need to systematize the hierarchy of verbalizers of the lexical-semantic field “democracy” in modern Ukrainian news discourse with the subsequent possibility of using the research results in investigations devoted to the lexical analysis of the texts of political, media and other discourses. The purpose of the study is to identify the verbalizers of the lexical-semantic field “democracy”, as well as the specifics of their interaction and functioning as the linguistic experience of the Ukrainian people in the texts of news reports. In modern linguistics, many attempts have been made to systematize the methods of researching lexical-semantic fields, many techniques and procedures for their analysis have been outlined. The authors of this article propose the use of the continuous sampling method, the analysis of dictionary definitions and the use of the istio SEO program to ensure the reliability of the obtained research results. The article carries out a comparative analysis of lexical units recorded in dictionary definitions of the concept of “democracy” and units of the near and far periphery of the lexical-semantic field, implemented in the texts of news reports. The method of identifying the lexical unit in the contextual environment with the help of SEO-program istio served as the main method of distinguishing the verbalizers of the analyzed field, since the context plays an important role in assigning the lexeme to the lexical-semantic fields. As a result of the application of these methods, it was found that the semantics of the lexical units of the immediate periphery of the noun “democracy” testifies that for the Ukrainian people “democracy” means people’s rule. In addition, it is proved that the units recorded on the far periphery of the lexical-semantic field “democracy” are intended to indicate the path to a democratic society and to verbalize the result of achieving democracy.

Выявлены вербализаторы лексико-семантического поля "демократия", а также специфику их взаимодействия и функционирования как языкового опыта украинского народа в текстах новостных сообщений. Проведен сопоставимый анализ лексических единиц, зафиксированных в словарных дефинициях понятия «демократия», и единиц ближней и дальней периферии лексико-семантического поля, реализованных в текстах новостных сообщений. Основным способом выделения вербализаторов анализируемого поля служил метод идентификации лексической единицы в контекстном окружении с помощью SEO-программы istio, поскольку контекст играет важную роль в отнесении лексемы именно к лексико-семантическим полям. Установлено, что семантика лексических единиц ближней периферии существительного «демократия» свидетельствует, что для украинского народа «демократия» – это народовластие. Кроме того, доказано, что единицы, зафиксированные на дальней периферии лексико-семантического поля «демократия», предназначены для обозначения пути к демократическому обществу и вербализации результата в достижении демократии.
Lexical-semantic field “democracy” as a means of organizing language experience
Чорний, І. Лексико-семантичне поле «демократія» як засіб організації мовного досвіду / Ігор Чорний, Ганна Малінська // Актуальні питання гуманітарних наук. - 2023. - Вип. 59, т. 3. - С. 161-165. - DOI: https://doi.org/10.24919/2308-4863/59-3-24.
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; лексико-семантичне поле; lexical-semantic field; лексико-семантическое поле; вербалізатор; verbalizer; вербализатор; дефініція; definition; дефиниция; лексична одиниця; lexical unit; лексическая единица; семантичне ядро; semantic core; семантическое ядро; демократія; democracy; демократия